Understanding the growth mechanism of wurtzite Cu2ZnSnS4 nanocrystals and the photodegradation properties. (5th June 2017) - Gao, Yao; Long, Fei; Wang, Jilin; Zhang, Jin; Mo, Shuyi; Zou, Zhengguang
Abstract: High quality wurtzite Cu2 ZnSnS4 (W-CZTS) nanocrystals (NCs) could be easily obtained by a simple green one-pot reaction process. Forming mechanism of the nanocrystals was investigated by XRD and Raman characterization. It demonstrated that forming W-CZTS started with nucleation of Cu2 S, then Sn 4 + diffused into Cu2 S to form the Cu2 SnS3, finally Zn 2 + diffused into Cu2 SnS3 to obtain W-CZTS. The optical and photocatalytic results of the W-CZTS NCs indicated that W-CZTS nanocrystals with copper-poor composition showed a better photocatalytic activity (the degradation of MB (methylene blue) could reach up to 81.79%). Moreover, this non-injected one-pot method could be further popularized and become a common approach to synthesize other quaternary wurtzite Cu2 MSnS4 (M = Fe 2 +, Co 2 +, Ni 2 +, Mn 2 +, Mg 2 + ) nanocrystals. Graphical abstract: Highlights: Wurtzite CZTS nanocrystals were synthesized via a green route. The growth mechanism of CZTS was investigated thoroughly. W-CZTS with Cu-poor composition has good photocatalytic degradation. Wurtzite Cu2 MSnS4 (M = Fe, Co, Ni, Mn, Mg) nanocrystal also has been synthesized.